Surgical teaching program for our senior medical students: room for improvement - Burgess, Annette (Dove Medical Press, 2014)
BACKGROUND: To ensure the quality of surgical teaching within our graduate entry medical program, a distinctive surgical teaching program has been developed at Sydney Medical School-Central. Spanning 2 years, the program includes lectures, small group surgical clinical tutorials, and formal student surgical grand rounds presentations, plus clinical placements and attendance in operating theaters. We sought to evaluate the effectiveness of the program. METHODS: In 2013, at the completion of year 4, all graduating students (n=54) were asked to complete an open and closed-ended questionnaire regarding their experience of the surgical program. RESULTS: A total of 44/54 (81%) students completed the questionnaire. Students reported a high level of engagement with their experience in clinical tutorials, and a moderate level of engagement in surgical lectures. Students found the clinical attachment to be the least useful method of teaching, with the surgical grand rounds presentation also eliciting a poor response from students. CONCLUSION: While both large group lectures and small group learner-centered teaching methods were highly valued by students, changes are needed to enhance clinical attachments for students in surgical wards. The benefits of students being made to feel part of a team during their surgical clinical attachments, along with adequate inpatient contact and formative feedback, should not be underestimated.